Student Readiness on the Blended Learning Modalities of the Philippine Merchant Marine Academy: An Assessment - Tripolca, Carolina O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This mixed-method research aimed to assess student readiness on the use of blended learning modalities at the Philippine Merchant Marine Academy. It examined the level of readiness towards self-directed learning, online student engagement, and the level of student satisfaction among the midshipmen to assess the effectiveness of these lesson delivery blends. 1CL, 3CL, and 4CL midshipmen officially enrolled in the 1st Semester of the School Year 2022-2023 were surveyed online to establish their demographic profile, their level of readiness in terms of self-directed learning and online student engagement readiness, and their level of student satisfaction. A semi-formal interview asked the faculty about their preferred blend or combination of modalities. The SPSS was utilized to analyze the results. When grouped according to year level, 4CL Midshipmen demonstrated lower Self-Directed Learning Readiness and Online Student Engagement than the senior cadets. When grouped according to program, BS Marine Transportation midshipmen were more self-directed and satisfied than the BS Marine Engineering midshipmen. Faculty favored the face-to-face and online asynchronous blend. Gleaning on the results of the study, an assessment tool (PMMA Blended Modalities Readiness Survey for Incoming 4CL Midshipmen) was proposed to address the identified challenges. The recommendations also included the incorporation of the proposed assessment tool into the Quality Operations Manual to serve as guidelines in the implementation of blended learning modalities. A competence assessment between colleges, strengthened collaboration between the IT department and the colleges, midshipmen digital literacy training, and faculty training on digital tools for online learning facilitation were also recommended.